Case series: raw, whole, plant-based nutrition protocol rapidly reverses symptoms in three women with systemic lupus erythematosus and Sjögren’s syndrome - Goldner, Brooke; Staffier, Kara Livingston (Frontiers in Nutrition, 2024)
Systemic lupus erythematosus (SLE) and Sjögren’s syndrome (SS) are chronic autoimmune diseases. Symptoms of SLE can vary widely but often include fatigue, pain, photosensitivity, and, in some cases, nephritis. SS is frequently characterized by extreme dry eye and mouth, resulting from damage to moisture-producing glands, and is often present in combination with SLE. While the health benefits of plant-based diets have been well-established with respect to weight and cardiometabolic outcomes, less research is available to support the role of diet in treatment and management of autoimmune disease. This case series presents three women with SLE and SS who adopted a nutrition protocol to reverse symptoms of autoimmune disease. The protocol emphasizes leafy greens, cruciferous vegetables, omega-3 polyunsaturated fatty acids, and water, and includes predominately raw foods. The three patients reported dramatic improvements in physical symptoms, with nearly all symptoms of SLE and SS resolving after 4 weeks or less of adhering to the protocol. All three patients have remained symptom-free, two of whom have remained symptom-free for 6+ years with no recent medication use. Patients and practitioners should be made aware of the promising possibility of food as medicine in the treatment of SLE and SS. Future research should explore whether dietary changes may be a potential treatment strategy for individuals suffering from severe symptoms and poor quality of life due to SLE and SS.